2010
DOI: 10.1021/jf904164t
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of S-Cysteinylated and S-Glutathionylated Thiol Precursors during Oxidation of Melon B. and Sauvignon blanc Musts

Abstract: Thiol precursor content in Melon B. and Sauvignon blanc grape juices obtained under vacuum was determined by quantifying cysteinylated and glutathionylated conjugates of 3-mercaptohexan-1-ol (3MH) and 4-methyl-4-mercaptopentan-2-one (4MMP). This characterization allowed the study of thiol precursor evolution during ripening of Sauvignon blanc grapes in several viticultural situations together with grape reaction product (GRP) and the main substrate of polyphenoloxidase, that is, caftaric acid. Concentration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
95
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(116 citation statements)
references
References 27 publications
18
95
3
Order By: Relevance
“…Some precursors in the juice have been identified as being cysteinylated or glutathionylated precursors (Tominaga et al, 1998b;Peyrot des Ganchos et al, 2002;Fedrizzi et al, 2009). However, studies have shown that these precursors account for only a fraction of the total amount of thiols present in the wine (Subileau et al, 2008a;Roland et al, 2010a;2010b), and no direct correlation between precursor concentration and the amount of free volatile thiols in the resulting wines has been observed Roland et al, 2011;Pinu et al, 2012). Other than release from precursors, the biogenesis of volatile thiols also has been proposed.…”
Section: Volatile Thiolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some precursors in the juice have been identified as being cysteinylated or glutathionylated precursors (Tominaga et al, 1998b;Peyrot des Ganchos et al, 2002;Fedrizzi et al, 2009). However, studies have shown that these precursors account for only a fraction of the total amount of thiols present in the wine (Subileau et al, 2008a;Roland et al, 2010a;2010b), and no direct correlation between precursor concentration and the amount of free volatile thiols in the resulting wines has been observed Roland et al, 2011;Pinu et al, 2012). Other than release from precursors, the biogenesis of volatile thiols also has been proposed.…”
Section: Volatile Thiolsmentioning
confidence: 99%
“…During winemaking, various processes can also be adapted to maximise precursor extraction and/or formation, as well the liberation of the thiol from the precursor. Practices such as mechanical harvesting, skin contact, pressure during pressing and oxygen exposure could significantly increase the precursor content in the juice and influence the volatile thiol concentration in the corresponding wines (Maggu et al, 2007;Patel et al, 2010;Roland et al, 2010b;Capone & Jeffery, 2011). The liberation of the volatile thiols from the respective precursors depends on conditions such as yeast strain, nitrogen availability and fermentation temperature (Murat et al, 2001a;Masneuf-Pomarède et al, 2006;Swiegers et al, 2006;Subileau et al, 2008b;Anfang et al, 2009;Harsch et al, 2013).…”
Section: Volatile Thiolsmentioning
confidence: 99%
“…The aroma molecules produced by Saccharomyces cerevisiae, including, among others, aldehydes, higher alcohols, medium-chain fatty acids (MCFAs), long-chain fatty acids, ethyl fatty acid esters, and acetate esters, give fruity and floral notes to wine (1,2). These volatile compounds are formed through a complex and dynamic metabolic process during fermentation, and many factors, such as grape variety, the nature of precursors (mainly amino acids), yeast strain, must treatments, and fermentation conditions, including oxygen, temperature, micronutrients, and nitrogen availability in the must, have been reported to control their production (1,(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…3MH bound as cysteinyl-conjugate (Cys-3MH), glutathionyl-conjugate (GSH-3MH) and also cysteinylglycin-conjugate (CysGly-3MH) have been reported [70,71]. 4MMP occurs in the grape and must as cysteine conjugate (Cys-4MMP) and glutathione conjugate (GSH-4MMP) [72,73]. Moreover, 3MH can be derived from either (E)-2-hexen-1-ol or (E)-2-hexenal [74,75].…”
Section: Varietal Thiol Precursorsmentioning
confidence: 99%
“…Through a lipoxygenase/lyase sequence active in the presence of oxygen, (E)-2-hexenal can be obtained from linolenic acid and converted to GSH-3MH by coupling with glutathione [75][76][77]. (E)-2-hexenal may act as a precursor when hydrogen sulfide is released in the early part of the fermentation [73,74,78]. Under aerobic conditions, S. cerevisiae is able to oxidize (E)-2-hexen-1-ol into (E)-2-hexenal, and the reverse process can occur under anaerobic conditions [77].…”
Section: Varietal Thiol Precursorsmentioning
confidence: 99%